Mechanical Evaluation of Two Hybrid Locking Plate Designs for Canine Pancarpal Arthrodesis. (2nd September 2021) - Zderic, Ivan; Varga, Peter; Styger, Ursula; Drenchev, Ludmil; Gueorguiev, Boyko; Asimus, Erik; Saunders, W. Brian; Kowaleski, Michael; Boudrieau, Randy J.; Dejardin, Loic M.
Abstract : Hybrid locking pancarpal arthrodesis plates were designed with either a round (RH) or an oval (OH) radiocarpal hole, the latter allowing varied screw positioning. Due to concerns about potential decreased structural properties of the OH design, our aim was to compare the mechanical behavior of the contrasting plates using combined finite element analysis (FEA) and mechanical testing. Pancarpal arthrodesis plates with RH or OH design were assigned to three fixation techniques (n = 6 ), prebent at 20°, and fixed to canine forelimb models with simulated radius and radiocarpal and 3rd metacarpal bones. OH plates were instrumented with a radiocarpal screw inserted either most proximal (OH-P) or most distal (OH-D). Specimens were axially loaded to 300 N over 10 ramped cycles at 0.5 Hz. Plate strains were measured with strain gauges placed at areas of highest deformations as predicted by FEA under identical loading conditions. FEA predicted the highest strains ( μ m/m) adjacent to the radiocarpal hole (2, 500 [RH], 2, 900 [OH-P/OH-D]) and plate bending point (2, 250 [RH], 1, 900 [OH-P/OH-D]). Experimentally, peak radiocarpal hole strains were not influenced by the OH screw position (3, 329 ± 443 [OH-P], 3, 222 ± 467 [OH-D]; P = 0.550 ) but were significantly higher compared to the RH design (2, 123 ± 154 ; P < 0.001 ). Peak strains at the bending point were significantly lower for OH-P (1, 792 ± 174 ) and OH-D (1, 806 ± 194 ) versus RH configurations (2, 158 ± 114 ) (P ≤ 0.006 ). OH plates demonstrated highest peak strains next to the radiocarpal hole and were associated with more heterogenous plate strain distribution. Structural weakening associated with radiocarpal OH plate design could result in decreased fixation strength and increased risk of plate fatigue failure.